2013
DOI: 10.1097/hco.0b013e32835fb7f3
|View full text |Cite
|
Sign up to set email alerts
|

Genetics and sudden death

Abstract: Advances in genetic sequencing technology are expected to significantly impact the clinical practice in the near future. Genetic testing represents a powerful tool for cause determination of arrhythmogenic cardiac diseases, efficient screening of family members, possible risk stratification and treatment choices. However, specific expertise is required for rational ordering and correct interpretation of the genetic screening results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 95 publications
0
8
0
Order By: Relevance
“…In addition, pathogenic variations in genes encoding structural proteins are responsible for cardiomyopathies (Hypertrophic Cardiomyopathy (HCM), Dilated Cardiomyopathy (DCM), and Arrhythmogenic Cardiomyopathy (AC), among others). These cardiomyopathies will usually present anatomo-morphological changes in the cardiac tissue, which can be diagnosed at autopsy [13], but recent reports have suggested that in infants they could also be potentially responsible for sudden death in the structurally normal heart [14, 15]. …”
Section: Introductionmentioning
confidence: 99%
“…In addition, pathogenic variations in genes encoding structural proteins are responsible for cardiomyopathies (Hypertrophic Cardiomyopathy (HCM), Dilated Cardiomyopathy (DCM), and Arrhythmogenic Cardiomyopathy (AC), among others). These cardiomyopathies will usually present anatomo-morphological changes in the cardiac tissue, which can be diagnosed at autopsy [13], but recent reports have suggested that in infants they could also be potentially responsible for sudden death in the structurally normal heart [14, 15]. …”
Section: Introductionmentioning
confidence: 99%
“…No mutations were found in the entire coding regions of the major LQTS associated genes (KCNQ1, KCNH2, SCN5A, KCNE1, KCNE2, and KCNJ2) and in ANK2 and RyR2 genes [3,4]. DNA was submitted to open reading frame/splice site mutational analysis on CAV3 gene by PCR and direct DNA sequencing, using coding region flanking primers (Table  1).…”
Section: Methodsmentioning
confidence: 99%
“…Congenital cardiac channelopathies and cardiomyopathies are known to play significant roles in SCD [2-4]. In the first cases genotype-phenotype correlation studies have identified most of the known disease-causing defects in genes encoding cardiac ion channels or other membrane components [3], while in the second cases cardiac structural abnormalities have been detected in subjects carrying mutations in sarcomeric proteins [4]. However, the identified variants commonly have reduced penetrance and are associated with heterogeneous clinical manifestations [2].…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to cases of intentional or suspected violent death, in instances when death occurred either suddenly, unexpectedly, or involving infants and the young [3], autopsy sampling focuses on the corpse's own substances to aid in determination of genetic markers and mutations which could be responsible for the cause or manner of death. From this point of view, the use of forensic genetics is not only strictly limited to purposes of identification, but may also be tasked by performing genetic tests for genes associated with disease [190,191]. Several specific or rare diseases may be linked to a particular pathological condition in cases of both positive and negative autopsy [189,192].…”
Section: Markers For Investigation Of Cause or Manner Of Death: Molecmentioning
confidence: 99%